Advances in library administration and organization. Vol. 24 - Nyce, James M.; Williams, Delmus Eugene; Garten, Edward D. (Emerald, 2006)
This volume includes a series of papers designed to help administrators meet the challenges of running organizations in an ambiguous climate. All of the articles address real management problems from a research perspective. The volume leads with a bibliometric study designed to help us understand the development of library science and higher education as disciplines and follows with a piece on the importance of place for libraries, a study of interactive services and professional culture within librarianship and then pieces on staff development and mentoring. Then, we look at the work processes of research librarians and management education for librarians. Finally, we look at service programs aimed at the Hispanic population and provide a location analysis of public libraries in Calcutta. As in past volume, this edition of ALAO includes an eclectic collection of strong papers that convey the results of the kind of research that managers need, mixing theory with a good dose of pragmaticism. The resulting volume adds significant value to our literature as the essays it contains treats classic problems in new ways.
Includes indexes.
Keywords: Library administration.; elektronické knihy; electronic books